The Influence of Working Capital and Labor on Income Levels at Anny Kebaya Boutique - Leni Indriana; RM. Rum Hendarmin; Reny Aziatul Pebriani (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study aims to examine the effect of working capital and labor on the level of income at Anny Kebaya Boutique in Palembang City. Data obtained from documentation, literature study, and surveys. The data were then analyzed using multiple linear regression. The results showed that both working capital and labor had a positive effect on the income level of Anny Kebaya boutique in Palembang City.